(untitled) (Comillas Journal of International Relations, 2023)
Every presidential election is shaped by determinant wedge issues, issues that are intentionally constructed to divide and polarize the electorate. When used correctly by candidates, these issues have the potential to mobilize the electorate towards one party or another. The U.S. presidential election of 2020 was characterized by the COVID-19 pandemic, the economic crisis resulting from it, accusations of electoral fraud and high levels of misinformation, as well as police brutality against minorities. This situation left a highly divided country and an electorate disappointed with the political institutions. The overall objective of this research is to explain the impact on voter mobilization, primarily, the impact wedge issues play, with the three specific issues of the campaign being: race issues, the prestige of the political institutions, and COVID-19.